Performance of growing heifers fed prairie hay and supplemented with alfalfa and(or) cooked molasses blocks of different protein concentrations - Bindel, D.J.; Hunter, R.D.; Nutsch, T.; Titgemeyer, Evan C.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Crossbred heifers (683 lb; n = 175; 30 pens) were used to evaluate alfalfa and cooked molasses block supplementation to prairie hay. Treatments were arranged in a 2×3 factorial with the factors being 0 or 5 lbs of alfalfa supplementation, and supplementation with no block or with low or high protein blocks (analyzed to contain 14.4 and 27.5% crude protein, respectively). Heifers had ad libitum access to prairie hay and salt. The experiment was 89 days, with heifers fed blocks for 84 days. During days 5 to 19, heifers had ad libitum access to blocks. Thereafter, access was restricted to 4 hours daily. No significant interactions occurred between alfalfa and blocks for intake or gain. Supplementation with alfalfa increased total forage intake by 49% (18.4 vs. 12.3 lb/day), and gains from –.39 lb/day to +.95 lb/day. Intake of the blocks was lower when alfalfa was supplemented (.76 vs. .98 lb/day). Heifers fed the high-protein block gained more weight (.46 lb/day) than those fed the lowprotein block (.25 lb/day) or no block (.12 lb/day). Heifers fed the high-protein block ate more forage (16.1 lb/day) than those fed the low-protein block (14.8 lb/day), with heifers fed no block (15.3 lb/day) being intermediate. Intake of block was greater for the high-protein (.93 lb/day) than for the low-protein block (.81 lb/day). Differences in forage intake accounted for much of the differences in performance among treatments.
Keywords: Beef; Heifers; Forage; Supplementation